Legal Protection on Sinking Victims of KM. Sinar Bangun Ship at Toba Lake in the Criminal Law Perspective - Riswan Munthe; Sri Hidayani (Budapest International Research and Critics University, 2020)
This research deals with legal protection on sinking victims Of Km Sinar Bangun Ship at Toba Lake in the criminal law perspective. This type of research used in this study is in the form of qualitative research with an empirical juridical research approach. The result shows that the form of legal protection given to the victims sinking of KM. Sinar Bangun in Toba Lake is that every accident victim is entitled to protection based on the provisions of the legislation, which is provided by the government in the form of direct social assistance in the form of cash through the Ministry of Social Affairs, types of compensation for victims in the form of death compensation, permanent disability compensation, and survivors. Each accident victim also received compensation from PT Jasa Raharja (Persero), the amount of which was determined by the miniser of finance, in addition to other legal protections the implementation of legal proceedings for the occurrence of criminal acts.